In-service Training, the Impact on Catering Officers’ Performance Mediated by Service Innovation Performance in Ghana - Senya, Elizabeth Kafui; Anakwa, Eunice Matey; Prebi, Herberta (Archives of Business Research, 2025)
This research examined in-service training, the impact on catering officers’ performance mediated by service innovation performance. The study employed survey research approach with structured questionnaires. The study used 284 participants. Structural equation modelling supported with maximum estimator with AMOS was used to establish the relationship between the variables. This result reveals a significant relationship between the employees’ perception of access to training, benefits of training, support for training and employee’s performance. There was mediation effect of service innovation performance between the relationship among the constructs. This research provides important management and theoretical implications for the hospitality industry.